Recovery from link failures in a Smart Grid communication network using OpenFlow - Gyllstrom, Daniel; Braga, Nicholas; Kurose, Jim (2014 IEEE International Conference on Smart Grid Communications (SmartGridComm), 2014)
In this paper, we design and evaluate algorithms for fast recovery from link failures in a smart grid communication network, addressing all three aspects of link failure recovery: (a) link failure detection, (b) algorithms for computing backup multicast trees, and (c) fast backup tree installation. To address (a), we design link-failure detection and reporting mechanisms that use OpenFlow to detect link failures when and where they occur inside the network. OpenFlow is an open source framework that cleanly separates the control and data planes for use in network management and control. For part (b), we formulate a new problem, Multicast Recycling, that computes backup multicast trees that aim to minimize control plane signaling overhead. We prove Multicast Recycling is at least NP-hard and present a corresponding approximation algorithm. Lastly, two control plane algorithms are proposed that signal data plane switches to install pre-computed backup trees. An optimized version of each installation algorithm is designed that finds a near minimum set of forwarding rules by sharing rules across multicast groups, thereby reducing backup tree install time and associated control state. We implement these algorithms in the POX OpenFlow controller and evaluate them using the Mininet emulator, quantifying control plane signaling and installation time.